G422 Dentists, doctors, nurses and neglect: do you see what i see?. (27th April 2015) - Olive, SM; Tuthill, DP; Maguire, S; Chadwick, BL; Hingston, EJ
Abstract : Background: Neglect is the most common form of child abuse in the UK. One area of neglect that is frequently overlooked is dental neglect. This rarely occurs alone and is part of a wider picture. Referrals for dental neglect are made infrequently by dentists; Possibly because no clear threshold for referral exists and they perceive concerns about the "Safeguarding" referrals system. Paediatric staff have limited oral health knowledge, and this combined with dentists reluctance to communicate concerns surrounding child protection, means that there is ample potential for dental neglect to be missed. Aims: We explored whether dentists, doctors and nurses, could agree on a threshold to act with regard to suspected dental neglect or child protection issues. Methods: A cross-sectional survey of hospital and community: doctors, dentists and nurses was conducted. Semi-structured interviews using a series of 5 vignettes involving oral health and child protection, focused on the following issues; An unkempt 4 year old with extensive dental caries who came on the third calling for a dental check up A 6 year old requiring one filling An obese, bullied, 14 year old with multiple carious cavities and dental erosions Bottle caries in a 4 year old whose 2 sisters have previously required dental extractions under general anaesthetic A 4 year old with substantial ear bruising who requires one filling Participants were asked to select from a list their dental and safeguarding actions. There was no child protection action required for case 2. Results: 150 responses (50 doctors, 50 dentists, 50 nurses) were obtained from 171 professionals approached. Just 3/14 dental practices agreed to participate. Less than 50% of doctors identified appropriate dental actions for 4/5 cases, and < 50% dentists identified appropriate safeguarding actions for 4/5 cases (Figures 1 and 2 ). Conclusion: Many dentists are uncertain about child protection issues and may not act upon abuse that appears obvious to other healthcare professionals. Likewise, doctors are uncertain about dental neglect. Minimal joint standards for dental neglect thresholds and the appropriate response need to be agreed.